Counterfuturisms and speculative temporalities: walking research-creation in school. Issue 6 (3rd July 2019) - Springgay, Stephanie; Truman, Sarah E.
Abstract: In education, walking has typically been used as a pedagogical strategy to move student bodies from one point to another, emphasizing creativity, discovery, health, and mobility. Although there are important reasons to advocate for walking in schools, the tenuous link between walking and creativity can be easily commodified and normalized by neoliberalism. Further, when walking is equated with discovery and mobility it enacts a progress narrative of time. To formulate an understanding of futurity that is counter to such normative articulations, we turn to scholars who conceive of space–time outside humanist reproductive logics. If chronos time accelerates, rendering some bodies and subjects successful in schools, while simultaneously pushing other bodies and subjects 'out of time, ' then different configurations of time are necessary in order to think otherwise about learning. In this paper, we discuss two walking research-creation projects in school contexts (elementary and secondary) that engage with counterfuturisms and queer enactments of temporality. Departing from an outcomes-based model of walking that is inscribed in neoliberal temporal schemes, we consider the complex ways that students can engage in walking as a method of inquiry into their spatio-temporal world-making.